Characterization of genes involved in lignin biosynthesis in Tectona grandis - Gómez, Esteban Galeano (2015)
Teak tree (Tectona grandis L.f.) has a high value in the timber trade for fabrication of woody products due to its extraordinary qualities of color, density and durability. Despite the importance of this species, genetic and molecular studies available are limited. Also, the lack of molecular information about secondary xylem and tree maturation has hindered genetic exploration of teak. Therefore, gene expression studies and transcriptomic profiling are essential to explore wood formation and lignin biosynthesis through the development and aging of vascular plants. Aiming the gene expression studies, it was essential to identify and clone reference genes for teak. Eight genes were tested, commonly used in qRT-PCR, including TgRP60S, TgCAC, TgACT, TgHIS3, TgSAND, TgTUB, TgUBQ and TgEF1a. Expression profiles of these genes were evaluated by qRT-PCR in six tissue and organ samples (leaf, flower, seedling, root, stem and branch secondary xylem). Stability validation by NormFinder, BestKeeper, geNorm and Delta Ct programs showed that TgUBQ and TgEF1a are the most stable genes to use as qRT-PCR reference genes in teak in the conditions tested. Due to the availability of 12- and 60-year-old teak trees, RNA-seq was performed in diferent organs (seedlings, leaves, flowers, root, stem and branch secondary xylem). A total of 462,260 transcripts were obtained by assembling with \"Trinity\" software. Also, 1,502 and 931 genes differentially expressed were identified for stem and branch secondary xylem, respectively, using DESeq program, and MYB transcription factors, which were characterized. TgMYB1 amino acid sequence displayed a predicted coiled-coil (CC) motif while TgMYB2, TgMYB3 and TgMYB4 showed R2R3-MYB domain. All of them were phylogenetically grouped with several gymnosperms and flowering plants. High expression of TgMYB1 and TgMYB4 in lignified tissues of 60-year-old trees was observed. In this work, the Cinnamyl Alcohol Dehydrogenase (CAD) gene family was also studied. One complete (TgCAD1) and three partial (TgCAD2 to TgCAD4) members were characterized. The four enzymes presented residues for catalytic and structural zinc action, NADPH binding and substrate specificity, consistent with the mechanism of alcohol dehydrogenases. TgCAD3 and TgCAD4 were highly expressed in young and mature sapwood and seem to be duplicated and highly related with lignin biosynthesis. Tree genetic improvement, marker-assisted selection and plant transformation seem to be promising lines of research for the data obtained from this research. This is the first study addressing gene characterization and expression, phylogeny and transcriptomic profiling in teak.